Mätramar för vederlagsmätning och timmersortering på sågverk - Henriksson, Kajsa (2014)
The measuring of logs is important in the sawmills process to the sawn products. The technology of automatic wood measurement is continuance developing. This study has the purpose to see how the different techniques and the routines works of measure frames for determining of wood value and sorting in sawmills. The study is performed as a literature study and a survey. The survey includes some of the Swedish sawmills that produce more than 10 000 cubic meters sawed products per year. The results of the study shows that the surveyed sawmills uses 2D shadow scanning, 3D log scanning technique and X- ray log scanner. They see benefits with each new developed measure frame technique. More detailed information can be given about the logs, which make that the logs early can be directed to the right final products and the logs sawing yield can be optimized. A new measure frame is a big economic investment. Advanced technique also demands more technical knowledge how to use all of the capacity of the measure frames. In order to handling the equipment education has been given by the suppliers. What was considered sufficient. One had the opinion that the education at operator level cold be done more thoroughly. The sawmills considered that the routines of control and maintenance works good. For future development the surveyed wishes for is fully automatic measurement for determining of wood value, more exactitude for length measuring. Continued development of X-ray scanning. Quicker be informed if unwanted objects are within the measuring range. Further development of control dummy and control routines for measuring under bark.